Trends in outdoor recreational activity among youth / Nurul Akmaniza Mohd Nasir ... [et al.] - Mohd Nasir, Nurul Akmaniza; Ahmad Kafri, Muhammad Tarmizi; Mohd Hashim, Nor Hanisah; Hahim, Nur Idzhainee (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Definition & Benefits - Recreation is an important aspect of human lives involving engaging in activities promoting relaxation, enjoyment and personal growth. Outdoor recreation can be defined as a recreational activity that requires voluntary participation during free time and involves interaction between natural environment and built resources (Beard. J.G., 1983). Recreation may vary depending on individual perspectives about the types of experiences that they would like to engage in leisure time. From watching movies at the cinema, taking your child to the public park, reading a book, cooking simple meals for your family, enjoying a stroll at the park or whatever activities that one chooses to enjoy during their free time. The diversity and depth of participation in recreation can be illustrated inside a three-dimensional box by representing different types of activities and experiences (McLean & Hurd, 2021). However, a distinct definition of recreation is much needed to guide the planning process in developing policies and highlighting the importance of recreation participation in the community.